Boiling water extraction of mangrove Sonneratia alba fruit as an antioxidant functional food: combined in vitro and pharmacoinformatics studies. - DOTULONG, Verly; MONTOLALU, Lita A. D. Y.; WONGGO, Djuhria; SANGER, Grace; DAMONGILALA, Lena; SYAHPUTRA, Rony Abdi; Nurkolis, Fahrul (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Extraction of antioxidants from mangrove fruit powder Sonneratia alba using boiling water as a solvent is very beneficial, because in addition to using a solvent that is safe for consumers, the results of this study can also be developed in the future as antioxidant functional foods. Aims and Methods: The purpose of this study was to study the antioxidant activity of boiling water extract of mangrove fruit S. albakindly in-vitro nor in-silico pharmacoinformatics. Results: The best results in this first stage were found in the treatment of mangrove fruit S. alba Sun drying extracted with boiling water for 5 minutes had the best antioxidant activity, namely IC50DPPH = 2.69 ± 0.32 µg/ml which is smaller than the positive control, namely vitamin C, which has IC50DPPH= 5.04 ± 0.16µg/ml. The best treatment in the first stage is continued in the second stage, namely GC-MS analysis to determine the type of compounds in the extract, and then do the analysis in-silico by means of molecular docking. The results of the GC-MS characterization showed 39 compounds that were in the category to be continued in the pharmacoinformatics via molecular docking process, with the docking results showing the bioactive compound Ergosterol; Estra-1,3,5(10)-trien-17ß-ol; Ergosta-5,8,22-trien-3-ol, (3ß,22E)- ; 9(11)-Dehydroergosterol tosylate ; Dasycarpidan-1-methanol, acetate (ester) shows a very promising value of binding affinity towards 4 protein targets, namely Cytochrome c peroxidase, Fibroblast collagenase, Human ROS1 Kinase Domain and Hyaluronidase with vitamin C as a control. Conclusion: Based on these findings, boiling water extract of mangrove fruit S. alba this can provide a good potential in the discovery and development of candidate new antioxidant compounds.